"A Coffee-Plantation is a Thing that Gets Hold of You and Does Not Let You Go": Plant-Writing in Karen Blixen's Out of Africa. Issue 4 (2nd October 2019) - Mortensen, Peter
Summary: One of the powerful but mostly overlooked productive forces in and behind Karen Blixen's Out of Africa (1937) is Coffea arabica, the coffee bush of Arabia. In this article, I first discuss the dominant anti-pastoral tendency in recent Blixen-criticism, which has classified Out of Africa as a neo-colonial text and reduced Blixen's interest in more-than-human nature to an expression of conservative ideology. I introduce two alternative concepts – "arabesque" and "phytographia" – that help me reposition Out of Africa and reconsider the significance of the text's many plant-references. Blixen's writing, in my understanding, holds a more timely interest and performs a more culturally productive function than is often assumed, especially insofar as it fore-grounds the life of many different plants and asks us to consider their powerful impact upon humanity. Read at a time when we are beginning to understand the disastrous implications of Western culture's deep-rooted "plant blindness", Blixen's text helps question the insignificance of plants and problematise the powerful conviction that humans and plants lead separate and unrelated lives.